Penerapan Math-In: Mathematics Adventure Game Terintergrasi Augmented Reality Sebagai Inovasi Media Literasi Matematika Berbasis Gamification - Aghits Zulvia Rachmawati; Isadur Rofiq (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Mathematical literacy is an important factor in forming quality human resources. Someone wholiterate (literate) mathematics is not just understanding mathematics but also being able to use it in solving everyday problems. The problem is, Indonesian students' mathematical literacy skills are still very low. Based on survey resultsTrends in International Mathematics and Science Study (TIMSS) which is held every 4 years, in 2011 Indonesia was in 36th position out of 40 countries and in 2015 it was ranked 45th out of 50 countries, with a score of 397 and still below the international average score, namely 500. In addition, In the Program for International Student Assessment (PISA) survey, Indonesia is ranked in the bottom 10 of 70 countries, namely in 62nd position. This shows that Indonesian students have not shown satisfactory achievements. Therefore, mathematical literacy skills need to be improved, one of which is through MATH-IN. MATH-IN is a medium for learning mathematics through exploring games oradventure game which is integrated with augmented reality. Through MATH-IN, users will be invited to explore and explore further about mathematics, starting from basic concepts to its application in the form of games. MATH-IN will be designed in the form of an application mobile which contains games adventure which focuses on concepts, and solving actual problems related to mathematics in them. Technology integration augmented reality MATH-IN is able to combine multimedia into the real world using electronic devices, making it possible to provide information to students anytime and anywhere. The application of learning methods through games has great potential in honing brain skills for solving problems as well as becoming a motivational learning medium that can build student motivation in learning. Through MATH-IN goalsquality education as one of the pillars of SDGs 2030 can be achieved.